An overview of recent developments in the description of Biblical Hebrew relevant to Bible translation - C. H. J. van der Merwe (Acta Theologica)
Describing the system of an ancient language like Biblical Hebrew is an enormous challenge. Biblical Hebrew scholars through the years concentrated on the formal features of limited data at their disposal. However, a new paradigm in the study of language has provided a fresh perspective on aspects of language that was up till now either not fully appreciated, misunderstood or not even noticed. Improved models of what people do with language, and which include the social, cognitive and cultural aspects of language, now provide explanations for linguistic expressions that translators up till now believed they may or should leave untranslated. These models, among other things, have shown that texts are more than strings of clauses, each with their own propositional content. There are a variety of linguistic signs that have no referential meaning or syntactic function, but act as overt navigation signals for the way in which the information is supposed to be processed. These signals do not only invoke a relationship between the clauses, or clusters of clauses, contained in a text, but may also involve the entire cognitive worlds of all the participants of the communicative situation. These developments may shed new light on the interpretation and translation of the Biblical text.